REHABILITATION PROGRAM FOR LOW BACK PAIN PATIENT WITH COMPRESSION FRACTURE: A CASE REPORT - Fikri Al Munawar; Rifalisanto (Lux Mensana: Journal of Scientific Health, 2026)
Introduction. Vertebral compression fractures (VCFs) in older adults frequently cause low back pain and functional limitations. Conservative care is the first-line option for stable fractures without neurological deficit, focusing on pain control and medical rehabilitation. Method.  The patient underwent medical rehabilitation twice a week for eight sessions over one month, followed by six months wearing of high LSO corset. Outcomes were assessed using pain scale and functional measures at weeks 8 and 16. Case Report. A 61-year-old woman sustained an L1 VCF after a low-energy fall onto her buttocks. She presented with chronic low back pain and activity limitation, without neurological deficit. Initial management consisted of analgesic optimization, education on safe activity, Infrared Ray (IRR) and conventional TENS, and a graded exercise program. After eight weeks, pain had improved but persisted during moderate activities; a high LSO lumbosacral corset was then prescribed to support posture. Result. After undergoing medical rehabilitation for 16 weeks, the patient showed significant recovery, pain was decreased from 7/10 to a manageable level with meaningful improvement even though radiology still showed persistent fracture deformity. Discussion. This case demonstrates that a conservative rehabilitation approach combining infrared therapy, TENS, structured exercises, and selective bracing can effectively reduce pain and improve function in an elderly patient with traumatic lumbar compression fracture. Current evidence supports multimodal conservative management for stable vertebral compression fractures, with emphasis on exercise programs and consideration of bone fragility treatment to prevent future fractures.